Management Of Principal's Strategy In Improving Teacher Performance At Senior High Schoool 2 Gowa - Nurul Hadijah; Syamsu Andi Kamaruddin; Wahira (International Journal of Education, Vocational and Social Science, 2025)
This study aims to describe and analyze the strategic management implemented by the principal in improving teacher performance at Senior High School 2 Gowa. The focus of this study includes strategic planning, strategic implementation, and strategic evaluation carried out by the principal. The approach used is a qualitative approach with a case study method. Data collection techniques are carried out through observation, in-depth interviews, and documentation. Informants in this study include the principal, vice principal, and teachers. The results of the study indicate that the principal of SMAN 2 Gowa applies a managerial strategy consisting of planning that includes determining the vision, mission, goals, strategies and policies. In the implementation stage, the principal involves all elements of the school through a participatory and collaborative approach. Furthermore, at the strategy evaluation stage, it is carried out periodically through academic supervision and teacher performance assessment. These strategies have proven effective in improving teacher performance, which is reflected in increased professionalism, discipline, and student learning outcomes. This study concludes that effective and participatory strategic management by the principal has a significant contribution to improving teacher performance.